MONETARY POLICY AND STOCK MARKET RETURNS IN UGANDA - Kalu, Emenike; Anselme, Bashamambire S.; Kirabo, Joseph K. B. (Journal Economics & Business Atmajaya Indonesia, 2019)
This study investigates the effect of monetary policy on stock market returns in Uganda using time series data for the period July 2011-December 2017. Specifically, the study evaluated the effect of central bank rate, Treasury bill rate and the inflation rate on stock market returns. The results of descriptive statistics establishes that mean value of the stock market returns is 1530.88 whereas the average central bank rate and treasury bill rate are 13.74 and 12.37 respectively while average consumer price index is 146.76. The results of the Augmented Dickey Fuller (ADF) and the Phillips-Perron (PP) test show that the variables are integrated of order 1. Estimates from regression model indicate that monetary policy strongly influences the stock market returns in Uganda. All the monetary policy variables considered in this study have significant effects on stock market returns in Uganda. A major policy implication of the findings is for stock market investors to monitor changes in monetary policy and factor them into their investment decisions.